1997
DOI: 10.1093/rheumatology/36.7.766
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of ankylosing spondylitis: a study of 100 patients.

Abstract: The outcome was studied in 100 patients with adult-onset primary ankylosing spondylitis (AS). After a mean disease duration of 16 yr, 51.5% of the patients were employed in full-time work. Cessation of work occurred at a mean disease duration of 15.6 yr, and was significantly associated with female sex, low levels of education, acute anterior uveitis, 'bamboo spine' and the co-existence of non-rheumatic diseases. Functional outcome was studied by analysing activities of daily living, and revealed similar findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
2
21

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(146 citation statements)
references
References 25 publications
10
113
2
21
Order By: Relevance
“…Serial blood samples were collected in anticoagulant tubes containing EDTA at specified times during the study (2,4,12,24,36,48,60,72,84,96,120,144,168,216,264,312,384, and 480 h after the first dose). Plasma samples were isolated from fresh blood by centrifugation and stored at -20 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serial blood samples were collected in anticoagulant tubes containing EDTA at specified times during the study (2,4,12,24,36,48,60,72,84,96,120,144,168,216,264,312,384, and 480 h after the first dose). Plasma samples were isolated from fresh blood by centrifugation and stored at -20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Many patients have localized new bone formation, ligamentous ossification, and progressive deformities that, without treatment, often lead to disability. A recent Norwegian study showed that the cessation of physical work in patients with AS occurred at an average disease duration of 15.6 years [2] . Currently, there is no cure for AS, but available therapies, such as individualized physical therapy and nonsteroidal anti-inflammatory drugs (NSAIDs), target symptoms and pain [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The late changes of ankylosis and osteoarthritis can lead to loss of function and total joint arthroplasty in 8-15% of patients. 46,93 Despite the increased ankylosis of joints, patients with AS commonly have decreased bone mineral density with consequent presentations of nontraumatic fractures in young, male patients. Osteoporosis of the femoral neck occurs in one third of patients, with osteopenia afflicting a further 41%.…”
Section: Neurosurg Focus / Volume 24 / January 2008mentioning
confidence: 99%
“…Волну-хина и соавт. [3] и ряда других авторов [13], хотя в литера-туре разброс данных по нетрудоспособности весьма велик. Так, S.M.…”
Section: результатыunclassified